Opening the common core : how to bring all students to college and career readiness - Burris, Carol Corbett; Garrity, Delia T. (Corwin Press, 2012)
Open the door to success with the CCSS This book shows how to leverage the Common Core State Standards (CCSS) to equip all students--not just high achievers--for college and career. The authors helped lead their district in closing achievement gaps and increasing the number of students who completed four-year college programs. The results of their efforts show a remarkable increase in both excellence and equity in the content areas due to applying the authors' research-based ACES framework: Acceleration rather than remediation Critical thinking Equity in education for all students Support Educators will find practical strategies that are applied and developed in model lessons linked to the CCSS and KSUS standards.